Negosiasi Lokalitas dalam Penafsiran Al-Qur'an: Strategi Stilistika Hamka dalam Tafsir Al-Azhar - Nur Afifah; Bilqis Shofiyana (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The relationship between the universality of the Qur'an and the cultural diversity of Muslim societies has become a major concern in contemporary Qur'anic studies. While numerous studies have examined contextual interpretation, limited attention has been given to how locality is constructed through the stylistic organization of exegetical discourse. This study investigates how Hamka negotiates locality in Tafsir Al-Azhar by examining the stylistic strategies through which Qur'anic meanings are communicated within the Indonesian socio-cultural context. Employing qualitative library research, the study analyzes selected passages of Tafsir Al-Azhar using textual analysis integrated with stylistic and contextual approaches. The analysis focuses on linguistic choices, interreligious discourse, and socio-historical narratives that mediate the relationship between revelation and local realities. The findings reveal three interrelated dimensions of stylistic localization. First, lexical localization utilizes vernacular expressions from Indonesian regional languages to bridge Arabic Qur'anic concepts with local linguistic consciousness. Second, dialogical localization employs interreligious comparisons to explain Islamic monotheism within Indonesia's plural religious landscape. Third, historical localization incorporates Indonesia's collective historical experience, particularly colonial memory, to strengthen the ethical relevance of Qur'anic teachings. These findings demonstrate that locality functions not merely as the background of interpretation but as an internal stylistic mechanism that shapes exegetical discourse. This study proposes Local Stylistics of Qur'anic Exegesis as a new analytical framework, arguing that locality is constructed through lexical, dialogical, and historical mediation rather than simply reflecting socio-cultural context. The proposed framework contributes to contemporary Qur'anic studies by offering a transferable model for analyzing vernacular tafsīr traditions across diverse Muslim societies.